(untitled) (Sebha University Conference Proceedings, 2022)
The research aims to identify the role of good administrative governance in reducing administrative and financial corruption in the faculty of arts at sebha university from the point of view of faculty members. The researchers adopted the descriptive analytical approach, and the administrative governance questionnaire was applied to a sample of (50) faculty members. The results of the research indicated that: the role of good administrative governance in reducing administrative and financial corruption in the faculty of arts at sebha university from the point of view of faculty members as a whole was on average. There are statistically significant differences in regulations and laws and participation in the role of good administrative governance in reducing administrative and financial corruption in the faculty of arts at sebha university. These differences are in favour of males at the expense of females. There are no differences in the field of transparency, administrative accountability, implementation of administrative governance, and the tool as a whole according to the gender variable. There are no statistically significant differences in the role of good administrative governance in reducing administrative and financial corruption in the faculty of arts sebha university from the point of view of faculty members according to the scientific qualification. Also, there are no statistically significant differences in the field of (regulations and laws, transparency, participation, and implementation of administrative governance) and the tool as a whole in the role of good administrative governance in reducing administrative and financial corruption in the faculty of arts at sebha university from the point of view of faculty members. According to the variable of the scientific degree, there are differences in the field of administrative accountability and the tool as a whole. And these differences in favour of the degree (lecturer), there are no statistically significant differences in the field of regulations and laws, transparency, participation and the tool as a whole in the role of good administrative governance in reducing administrative and financial corruption in the faculty of arts at sebha university from the point of view of faculty members according to the variable of years of experience. And there are differences in the field of administrative accountability and implementation of administrative governance. These differences are in favour of faculty members whose experience is less than 10 years.